Pengaruh Computer-Self Efficacy, Perceive Usefulness dan Perceived Ease of Use Terhadap Pemanfaatan Simrs Oleh Perawat - Dinna Guswita Gultom; Kaiman Turnip; Nina Siti Salmaniah Siregar (Mahesa Research Center, 2022)
This study aims to determine the effect of computer self-efficacy, perceived usefulness and perceived ease of use on the use of SIMRS by nurses at RSU. Haji Medan. This study uses a quantitative research design with data collection techniques using the questionnaire method. The sampling technique used probability sampling type Cluster Sampling as many as 60 samples of nurses from a total population of 204 nurses in inpatient, outpatient and emergency department installations. The data analysis technique used in this study uses multiple regression analysis, t test to determine the effect between variables partially, and F test to determine the effect between variables simultaneously. The study was conducted from April to June 2021 with the results of the study finding that the computer self-efficacy variable did not partially affect the use of SIMRS. The purpose of using SIMRS to realize integrated documentation will not be achieved if the system has not been fully adopted by other Health Human Resources even though nurses are confident in their ability to use the system. Meanwhile, the variables perceived usefulness and perceived ease of use have a positive effect on the utilization of SIMRS by nurses in completing their tasks.